Population fluctuation of phytophagous insects in kale, Brassica oleracea var. sabellica L. (Brassicaceae) in Guanajuato, Mexico - Martínez-Sánchez, Cinthia; Aguirre-Mancilla, Cesar L.; Flores-Gómez, Carlos A.; González-Pacheco, Blanca E.; Romero-Rosales, Teolincacihuatl; Rodríguez Pimentel, Juan Gabriel (Revista Colombiana de Entomología, 2026)
Kale is considered as a superfood, and it is a crop in expansion, so its production requires to analyze all the agronomic considerations and interactions within agroecosystems; in the present study, the population dynamics of phytophagous insects associated with kale (Brassica oleracea var. sabellica) cultivation was analyzed, aiming to determine their fluctuation, identify the most relevant species, and relationship with yield. The research was conducted in the Soria community, municipality of Comonfort, Guanajuato, Mexico, under an agroecological production system. A total of 36 plants of the “chino” variety were sampled on 14 evaluation dates, between 15 and 120 days after planting. Nine phytophagous species belonging to the orders Hemiptera, Lepidoptera, and Coleoptera were identified, among which Myzus persicae, Lipaphis erysimi, Murgantia histrionica, Leptophobia aripa, Trichoplusia ni, Plutella xylostella, Evergestis rimosalis, Diabrotica undecimpunctata, and D. balteata stood out. The highest population densities were observed in Lepidoptera larvae, particularly during the evaluations between 88 and 120 days after transplanting. Regression analyses revealed a negative correlation between the presence of L. aripa and E. rimosalis and yield (r > 0.83; p < 0.05), with direct impact on the production and commercial quality of kale. Conversely, P. xylostella and T. ni showed irregular fluctuations. The results emphasize the necessity of adjusting the frequency and timing of leaf harvesting as part of an integrated pest management strategy, key to reduce the pressure from phytophagous insects and promoting sustainability in leafy vegetable production.